Effects of Non-Protein Nitrogen Sources on In Vitro Rumen Fermentation Characteristics and Microbial Diversity - Zhu, Jinjia; Ren, Ao; Jiao, Jinzhen; Shen, Weijun; Yang, Lingyuan; Zhou, Chuanshe; Tan, Zhiliang (Frontiers in Animal Science, 2022)
Here, the effects of non-protein nitrogen sources on fermentation parameters and microbial diversity were explored using three fistula goats as rumen fluid donors. The experiments involved six fermenters in a replicated 3 × 3 Latin square design with three dietary non-protein sources [ammonium chloride (A), biuret (B), and glutamine (G)] as treatment factors. A dual-flow continuous culture fermentation system was used. Microbial protein content in group B was significantly lower than that in the other two groups (P < 0.05). Ammonia nitrogen concentration significantly differed among the three groups (P < 0.01), following the order of G > A > B group. The acetate-to-propionate ratio in group G was significantly lower than that in the other two groups (P < 0.01). At the phylum level, the relative abundances of Cyanobacteria, Elusimicrobia, and Armatimonadetes were the highest in group G, being significantly higher than those in group B (P < 0.05). At the genus level, the relative abundance of Ruminococcus_1 was significantly higher in group A than in group B (P < 0.05). Overall, glutamine shifted the fermentation pathway from acetate to propionate, and the lower microbial crude protein content and relative abundances of the major fiber-degrading bacteria Ruminococcus_1 and protein-degrading bacteria Prevotellaceae_UCG-001 in group B indicate that biuret is not suitable as a dietary non-protein nitrogen source.